Influence of Culture Media on the Radiation Resistance of Micrococcus radiodurans - Krabbenhoft, K. L. (1967)
The addition of NZ-case (a tryptic digest of casein) to a growth medium (PC) consisting of tryptone, glucose, and yeast extract caused a significant decrease in γ radiation resistance of Micrococcus radiodurans. The level of radiation resistance was inversely related to the concentration of NZ-case. The ld(50) for this organism was approximately 700 krad when grown in tryptone, glucose, yeast extract, and dl-methionine (TGYM) broth, but it was approximately one-half as resistant when grown in a PC medium containing 0.5% NZ-case (PCNZ). The resistance to ultraviolet light was also reduced. Cultures transferred from PCNZ to TGYM media regained the high level of resistance.